L’histoire par les lieux : odonymes et monuments comme documents historiques pour les Antilles françaises et la Guyane ? - Jean Moomou (Caravelle)
The article focuses more particularly on an analysis of odonyms (streets, boulevards, schools, etc.) and on the monuments that can be found in the public areas of main cities as well as in the smaller towns of these territories, between the 18th and 20th centuries. The proposed study aims to show how odonyms and monuments in the public space can be seen as materials to approach the history of the West Indies and Guyana; to underline the limits of such a device which doesn’t allow the elaboration of a general theory.